African goat genetic resources, diversity and unique features - Okpeku, M.; Bemji, M.N.; Houaga, I.; Fantazi, K.; Banda, L.J.; Gondwe, T.; Chenyambuga, S.; Elnahta, S.A.; Mthiyane, D.M.N.; Belay, S.; Dessie, Tadelle; Adewumi, T.S.; et al. (Springer, 2025)
This chapter introduces indigenous African goats, exploring their origins of domestication, dispersal and distribution across the African continent. The first two sections provide a general overview (Sects. 5.1 and 5.2). The following three sections (Sects. 5.3, 5.4, and 5.5) are devoted to the history of domestication, dispersal and distribution, tracing the journey from the centres of domestication to their present-day locations. Section 5.5 focuses on the characterisation of available genetic diversity, categorising goats into three major groups: indigenous, exotic and composite breeds. Each subsection examines the origin, distribution, classification, physical characteristics, adaptive characteristics and production characteristics of named breeds. Section 5.6 discusses the characterisation of genetic diversity in African goats. It highlights the role of modern molecular markers in the characterisation of genetic diversity and the utilisation of known gene regions to understand adaptation, physiology and production functions in goats. Section 5.7 presents an overview of indigenous knowledge on the utilisation of various goat products. The chapter concludes with a future outlook (Sect. 5.8) on African goat genetic resources, utilisation and potential conservation strategies for the present and future.